2009
DOI: 10.1016/j.biopsych.2008.11.030
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetic Resonance Imaging Study of the Cerebellar Vermis in Chronically Treated and Treatment-Naïve Children with Attention-Deficit/Hyperactivity Disorder Combined Type

Abstract: Background-Because of its dense connections to the prefrontal cortex and basal ganglia, the cerebellum is thought to play an important role in cognition. Numerous MRI studies have found abnormalities in the cerebellum in children with ADHD. While some studies in animal and human models suggest that the certain brain structures are affected by chronic stimulant medication, it is unclear whether the cerebellum is also affected. The purpose of the current study was to determine if cerebellar morphology was differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 30 publications
3
84
0
Order By: Relevance
“…Castellanos et al demonstrated that, among children with ADHD, those treated with stimulants did not differ from controls in white matter volumes, whereas in medication-naïve children with ADHD, white matter volume was reduced compared to controls (Castellanos et al 2002). More recently, stimulant-related "normalization" has been reported for children with ADHD in right anterior cingulate and bilateral caudate volumes (i.e., volumes closer to controls compared to those untreated children with ADHD) (Pliszka et al 2006), and for crosssectional area of posterior interior cerebellar vermis (Bledsoe et al 2009). In a similar investigation, Sobel et al examined basal ganglia surface morphology and the effects of stimulant medication treatment in children with ADHD.…”
Section: Treatment With Stimulant Medication and Volumetrymentioning
confidence: 97%
“…Castellanos et al demonstrated that, among children with ADHD, those treated with stimulants did not differ from controls in white matter volumes, whereas in medication-naïve children with ADHD, white matter volume was reduced compared to controls (Castellanos et al 2002). More recently, stimulant-related "normalization" has been reported for children with ADHD in right anterior cingulate and bilateral caudate volumes (i.e., volumes closer to controls compared to those untreated children with ADHD) (Pliszka et al 2006), and for crosssectional area of posterior interior cerebellar vermis (Bledsoe et al 2009). In a similar investigation, Sobel et al examined basal ganglia surface morphology and the effects of stimulant medication treatment in children with ADHD.…”
Section: Treatment With Stimulant Medication and Volumetrymentioning
confidence: 97%
“…Prospective studies further examining this possibility, incorporating objective measures of hyperactivity, would be of interest. Multiple studies have reported structural abnormalities of the cerebellum in ADHD patients (Berquin et al, 1998;Castellanos et al, 2002;Mostofsky et al, 1998;Valera et al, 2007;Bledsoe et al, 2009). Overall, although some discrepancies exist, the weight of the evidence indicates that both global and regional volumetric abnormalities occur in ADHD.…”
Section: Selected Adhd Imaging Datamentioning
confidence: 99%
“…A 5-year longitudinal study found smaller total white matter volume in unmedicated compared with medicated ADHD children (Castellanos et al 2002). More normative volumes in several brain areas, i.e., the inferior frontal cortex (Shaw et al 2009), cerebellum (Bledsoe et al 2009), basal ganglia (Sobel et al 2010), and anterior cingulate cortex have been found in chronically treated compared with unmedicated children. Pliszka et al (2006) reported more pronounced differences in the anterior cingulate cortex and ventrolateral prefrontal cortex during an inhibition task in drug-naïve ADHD compared with healthy children, but direct comparisons between drug-naïve subjects and subjects with a history of psychostimulant treatment revealed no differences.…”
Section: Introductionmentioning
confidence: 99%